THE CONTRIBUTION OF UNIVERSITY STUDENT DORMITORIES TO THE FORMATION OF STUDENT CHARACTER VALUES - Musadad, Ahmad; Nasik, Khoirun; Nahidloh, Shofiyun; Dwi Saputro, Sigit; Rasiman, Iman; Pujiati, Tri (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Challenges to character education in higher education are issues that must be resolved in an effort to shape student character. Student dormitories are considered a space for character development outside of academic classes. This study focuses on the contribution of student dormitories in shaping student character education with an emphasis on the aspects of orderly, polite, and caring. Objective: This study was conducted to see the influence of the dormitory environment in shaping student character in higher education holistically. Methods: This study used a mixed method approach. Results: The results showed that the contribution of student dormitories has a significant role in shaping student character, especially in the Faculty of Islamic Studies, through a pesantren-based education model that integrates moral, spiritual, and social values in students' daily lives. The t-test results show that the significance value of the influence of the dormitory contribution on character is below 0.05, this means that there is a significant influence between the dormitory contribution on student character building. The regression equation results show Y = 37.423 + 0.696X. This means that an increase in dormitory contribution by 1% leads to a 0.696% improvement in character development. Conclusion: The results of this study contribute that the implementation of a dormitory curriculum that prioritises character education as a whole is different from the approach generally found in other universities that focus more on academic aspects alone.